TRAUMA AIRWAY MANAGEMENT TRAINING OF MEDICAL STUDENTS: BLENDED LEARNING COMPARED TO LIVE LEARNING: Teaching trauma airway management to medical students - Rodrigues Viana, Rita; Baptista, Sérgio; Alexandrino , Henrique; Vaz, Fábio; Madeira, Filipa; Carvalho, Vanessa (Journal of the Portuguese Society of Anesthesiology, 2023)
Introduction: Blended learning gained emphasis with the COVID-19 pandemic. The main objective of this study was to compare blended to live learning regarding knowledge and skills acquisition in airway approach. Secondly, we intended to assess the participants' perception regarding the different formats and the role of simulation in undergraduate medical teaching of airway skills. Finally, we aimed to create and validate an assessment tool for airway management skills. Methods: A randomized controlled trial was conducted with sixteen medical students. The control group attended a live lecture on airway approach in trauma. The study group had access to the content in an asynchronous online format. All participants were submitted to a live practical session, a knowledge test, and a skill evaluation. The latter was analyzed by three external observers through a Trauma Airway Assessment Tool. The results were evaluated using the Mann-Whitney test. For the assessment tool validation, the intraclass correlation coefficient was calculated. All candidates replied to an opinion survey, which was evaluated using the Mann-Whitney and Wilcoxon tests. Results: There was no significant difference between the theoretical and practical evaluations of both groups (sig>0.05). The agreement between the observers was moderate. The opinion’s survey showed that students prefer blended learning. Discussion and Conclusion: The teaching of the airway approach in trauma settings can be performed through blended format without impairing student learning. The Trauma Airway Assessment Tool is useful but needs to be improved. Students are motivated in blended learning and the integration of simulation into medical education.